1983
DOI: 10.1111/j.1365-2044.1983.tb14031.x
|View full text |Cite
|
Sign up to set email alerts
|

The determination of an effective cricoid pressure

Abstract: A study of cricoid pressure was undertaken to relate the applied cricoid force with the resulting intraluminal cricopharyngeal (or oesophageal) pressure. The results indicate that whilst there was a wide range in normal adults a cricoid force of 44 N was judged to be effective in protecting the majority of adult patients from regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(50 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…It has been demonstrated that the upper oesophagus can be occluded by the correct application of cricoid force at or in excess of 30 newtons (N). [14][15][16] Wraight et al extrapolated from his research that a force of 44 N would suffice for instances of above average intragastric pressure. 14 Force in excess of 44 N carries an increased risk of airway obstruction, which becomes significant should there be a failure to intubate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the upper oesophagus can be occluded by the correct application of cricoid force at or in excess of 30 newtons (N). [14][15][16] Wraight et al extrapolated from his research that a force of 44 N would suffice for instances of above average intragastric pressure. 14 Force in excess of 44 N carries an increased risk of airway obstruction, which becomes significant should there be a failure to intubate.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Wraight et al extrapolated from his research that a force of 44 N would suffice for instances of above average intragastric pressure. 14 Force in excess of 44 N carries an increased risk of airway obstruction, which becomes significant should there be a failure to intubate. This level of force might directly impede intubation and is implicated in some case reports of soft tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…This force was recommended by Wraight et al . [18] as a cricoid force that would prevent regurgitation with a theoretical maximum gastric pressure of 59 mm of Hg in 50% of patients. However, it has been found that excessive force, especially > 40N, can compromise airway patency and cause difficulty with tracheal intubation.…”
Section: Does Cp Cause Problems With the Airway?mentioning
confidence: 99%
“…[19] Wraight et al . [18] have shown that 34N occluded a manometry catheter behind the cricoid cartilage at pressure >30 mm of Hg in all patients. In another study, by Vanner et al .,[20] cricoid force of 30N occluded the manometry catheter with a pressure >25 mm of Hg in all patients.…”
Section: Can Less Cp Force Prevent Regurgitation?mentioning
confidence: 99%
“…The amount of force used by the cricoid operator is a crucial factor in proper application of CP. A force in the range of 30 - 40 Newtons (N) applied to the cricoid ring is generally accepted as sufficient to occlude the oesophagus [5,12,16-18], preventing regurgitation of gastric contents. Studies have revealed that the knowledge of cricoid force theory and concept of the forces required is poor amongst both anaesthetic and ED staff [19-31].…”
Section: Introductionmentioning
confidence: 99%